Penerapan Pengelolaan Dana Hibah Pengadaan Sarana dan Prasarana di Biro Kesejahteraan Rakyat Sekretariat Daerah Provinsi Jawa Timur - Nurdihansyah, Muhammad Raihan Adji; Arundinasari, Indira (IAI Nasional Laa Roiba Bogor, 2024)
Grant funds have become an important instrument in supporting the development of various sectors, including education and community welfare. The aim of this research is to study the role and influence of grant funds in improving these sectors. In addition, this research explains the process of applying for grant funds from the grant application stage to the grant accountability reporting stage. Domestic Regulation Number 23 of 2011 concerning guidelines for providing grants and social assistance from the APBN states that the aim of managing grants and social assistance is to ensure orderly administration, high accountability and management transparency. The allocation of social welfare spending in provincial and city government budgets in Indonesia is an implementation of social development which aims to reduce poverty not only in terms of income and consumption, but also in terms of social and environmental aspects. It can be seen that the flow of grant aid has a coherent procedure starting from the application to the disbursement process. There is a system that regulates the flow of grant aid so that the application process is easier.